PERAN SYLLABIC METHOD DALAM PENGEMBANGAN KOSAKATA BAHASA INGGRIS ANAK - Andri Astuti, S.Pd.I., M.Pd.I; Maisarah Gusvita, S.Pd.I, M.Pd; Chichi Apriani; Uswatun Khasanah; Indri Nursamawati; Ngaisatun; Putri Melati (As-Sulthan Journal of Education, 2026)
Vocabulary mastery is a fundamental aspect of English language learning for children, as it serves as the foundation for developing other language skills. However, phonological differences between Indonesian and English often cause difficulties in reading and pronunciation. This article aims to examine the role of the syllabic method in developing children’s English vocabulary through a Community Service Program (PKM) using a Small Group Study approach. The program was conducted in Tenam Village, Muara Bulian District, Batang Hari Regency, involving 3 out of 15 children who experienced difficulties in reading and pronouncing English vocabulary. The method employed consisted of training and mentoring conducted over nine meetings, encompassing preparation, implementation, and evaluation stages. The results indicate that the application of the syllabic method improved children’s reading, writing, and pronunciation skills, with the most significant improvement observed in pronunciation. These findings suggest that the syllabic method is an effective and appropriate approach for enhancing English vocabulary learning among young learners.